Problem Based Learning with ICT Based with Learning Creativity to Improve History Learning Achievement - Sukestini, Erna; Fatirul, Achmad Noor; Hartono, Hartono (Jurnal Pendidikan dan Pengajaran, 2020)
The teaching and learning process were boring and made students’ participation in the classroom learning activities less enthusiastic that could make students’ achievement’ decreased. The main objective of this study was to analyze the effect of the Problem Based Learning model-based ICT with students' creativity on historical learning achievement. This research was a quasi-experimental study with a factorial design. The samples of this study were 4 classes, and each class consist of 34 students and total 170 students. The instrument used were learning outcome tests in the form of multiple-choice questions and creativity tests in the form of essay questions. The data on this study were analyzed using inferential statistics with the Two Way Anova technique formula. The results of this study obtained Fcount = 28,908 with a significance value of 0,000 less than 0,05, obtained Fcount = 4,623 with a significance value of 0,033 less than 0,05, the obtained Fcount = 6,060 with a significance value of 0,015 less than 0,05. From the result of this study, it can be implied to improve historical learning achievement, problem-based learning models can be used as an alternative model to create an interactive learning environment.